Aumolertinib with carboplatin–pemetrexed versus aumolertinib for nonsmall cell lung cancer with EGFR and concomitant tumor suppressor genes (ACROSS2): An open‐label, multicenter, randomized phase 3 study - Jian‐Chun Duan; Jia Zhong; Bo‐Yang Sun; Wen‐Hua Zhao; Lin Wu; Kai‐Lun Fei; Qian Chu; Qi‐Sen Guo; Qi‐Bin Song; Yan Yu; Da‐Xing Zhu; Xin‐Yan Liu; et al. (CA: A Cancer Journal for Clinicians, 2026)
ABSTRACT Third‐generation epidermal growth factor receptor–tyrosine kinase inhibitors (EGFR‐TKIs) are standard first‐line therapy for advanced, EGFR ‐mutated nonsmall cell lung cancer (NSCLC). However, their benefit is limited in patients who have co‐existing tumor suppressor gene (TSG) mutations, highlighting a need for intensified strategies to improve outcomes. ACROSS2 (ClinicalTrials.gov identifier NCT04500717) is the first prospective, multicenter, randomized phase 3 study to compare the third‐generation EGFR‐TKI aumolertinib in combination with carboplatin–pemetrexed versus aumolertinib monotherapy in patients who had NSCLC with EGFR mutations and concomitant TSG mutations. In total, 126 patients were enrolled and randomly assigned to either combination therapy ( n = 62) or monotherapy ( n = 64). The primary end point was median progression‐free survival (PFS). At a median follow‐up of 25.3 months, combination therapy significantly prolonged median PFS compared with monotherapy (19.78 vs 16.53 months; hazard ratio, 0.58; 95% confidence interval, 0.34–0.97). Landmark PFS rates at 12, 18, and 24 months were 78.7% versus 65.3%, 67.2% versus 40.8%, and 41.0% versus 29.9%, respectively. Subgroup analyses demonstrated a clear PFS benefit in patients who had co‐existing tumor protein p53 ( TP53 ) mutations. Grade 3 or greater adverse events occurred in 25.9% of patients who received combination therapy versus 17.2% of those who received monotherapy; no drug‐related deaths were observed. Overall survival data were immature (data maturity, 4%). The ACROSS2 trial provides the first prospective evidence supporting a genotype‐directed, chemotherapy‐targeted intensification approach favoring aumolertinib plus carboplatin–pemetrexed for this molecularly defined population.